Public opinion on cash transfer for children and adolescents in Mexico: Clear support for greater coverage and adequac - Blofield, Merike (2023)
Child poverty is a multidimensional challenge and decades of evidence show that access to regular cash transfers can provide simple and effective protection against poverty, especially extreme poverty. In this context, it is surprising how little is known about how public opinion perceives these programs, both in Mexico and in Latin America more broadly. As part of a comparative study of public opinion in seven Latin American countries, a nationally representative telephone survey in Mexico conducted in May 2022 indicates that cash transfer programs aimed at children and adolescents have very high support (90%). In addition, 96% support setting the value of the transfers to at least the cost of the basic food basket. Finally, a majority (56%) would extend transfers to include at least all children and adolescents in poverty, while 43% support restricting the program to those in extreme poverty.